Asthma exacerbation in children: relationship among pollens, weather, and air pollution - Tosca, M A; Ruffoni, S; Canonica, G W; Ciprandi, G (Allergologia et immunopathologia, 2014)
Asthma exacerbation is an episode of (sub)acute worsening of asthmatic symptoms. Exacerbation may depend on environmental factors. The present study investigated emergency calls for asthma exacerbation in children, analysing: i) their trend over the course of time; and ii) their possible relationship with environmental factors, including pollen count, meteorological parameters, and air pollution. Emergency calls for exacerbation were recorded for 10 years (from 2002 to 2011) in Genoa (Italy). Betulaceae, Urticaceae, Gramineae, and Oleaceae pollen counts were measured. Meteorological parameters and air pollutants were also measured in the same area and for the same period. The number of emergency calls did not significantly modify during the time studied. Two main peaks were detected: during the autumn and the spring. Wind speed significantly diminished as did most air pollutants. There were significant and relevant relationships between emergency calls and: pollens during the spring (r = 0.498), rainfall (r = 0.818), wind speed (r = 0.727), and air pollutants (r = 0.622 for SO2; r = 0.699 for NO; r = 0.58 for NO2). This 10-year survey demonstrates that: (i) asthma exacerbations did not diminish over the time; (ii) there were seasonal peaks (autumn and spring); (iii) pollens (mainly Parietaria), wind speed and rainfall, SO2, NO, O3 and NO2 were strongly associated with asthma exacerbations in children in this area. Therefore, asthma exacerbations may significantly depend on environmental variations.